Mobile-Based Digital Car Plate Number for Future Automotive Industry - Malathy, Batumalay; Linesh Raj, Kumar Chandran; Chitra, Batumalai; Deshinta, Arrova Dewi (INTI International University, 2019)
Number plate is the identity of a car. The existing number utilizes an old system that is prepared manually. Besides that, the road tax renewal is another manual process where users have to wait for a long queue or learn to use online option. In this proposed system, wireless application using digital plate was configured to help manage the renewal process. Using this proposed system, users are able to update their road tax by utilizing the digital screen, hence, reduces the time and resources needed. The system applies a serial input and there is no need to stick road tax on the windshield. In addition, there is an option where user can trigger an alert to indicate if the car is stolen and establish a panic situation by activating the car siren automatically in order to alert the nearby security officers.